-4-2(-b-7)=6b-22

Simple and best practice solution for -4-2(-b-7)=6b-22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4-2(-b-7)=6b-22 equation:


Simplifying
-4 + -2(-1b + -7) = 6b + -22

Reorder the terms:
-4 + -2(-7 + -1b) = 6b + -22
-4 + (-7 * -2 + -1b * -2) = 6b + -22
-4 + (14 + 2b) = 6b + -22

Combine like terms: -4 + 14 = 10
10 + 2b = 6b + -22

Reorder the terms:
10 + 2b = -22 + 6b

Solving
10 + 2b = -22 + 6b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-6b' to each side of the equation.
10 + 2b + -6b = -22 + 6b + -6b

Combine like terms: 2b + -6b = -4b
10 + -4b = -22 + 6b + -6b

Combine like terms: 6b + -6b = 0
10 + -4b = -22 + 0
10 + -4b = -22

Add '-10' to each side of the equation.
10 + -10 + -4b = -22 + -10

Combine like terms: 10 + -10 = 0
0 + -4b = -22 + -10
-4b = -22 + -10

Combine like terms: -22 + -10 = -32
-4b = -32

Divide each side by '-4'.
b = 8

Simplifying
b = 8

See similar equations:

| -7+9f=-1+10f | | -8(2x-5)+3x=4(x+7)-107 | | 6+x=6.1x | | -4-3(-b-7)=6b-22 | | -7-5v=-2(3v+6) | | 3x-2(x-1)=3(x+5) | | 6x+7-4x=8+7x-12 | | 4+3(5x+14)=39x-8 | | 6(3a+1)-30=3(2a+1) | | -65/5= | | 3(x+4)=-5 | | r^2-12r+33=8 | | 5x+10+4x-10=90 | | 6x-5/6=7/8 | | 3a-2a+2b-4+8a-b= | | .0009873= | | 5s^2-44s-9= | | x-1+10=3x-1 | | -24/4 | | |5-26|*(-3)/(-3) | | 18-3y=0 | | 16.87=1x+1.5x | | 6s=66 | | -17*3= | | 7.5y+1.6-2= | | 5n-6=5n-5 | | 13.1=-(k+6.2) | | 6t+5=5t | | 6(x+20)=168 | | 8*7(-6)= | | 20007-78= | | y(1+8x)=4-3x |

Equations solver categories